PENGARUH KONVERGENSI IFRS TERHADAP LIABILITAS DAN PENGARUHNYA TERHADAP LAPORAN KONSOLIDASI - Batsyeba, Eka Wury (Jurnal Akuntansi AKUNESA, 2013)
IFRS convergence is a Financial Accounting Standards followed by Indonesia as a form of Indonesia's participation in the G-20 (Group of Twenty Finance Ministers and Central Bank Governors). IFRS convergence has an influence on the presentation of consolidated financial reporting in which there is a liability account. With the convergence of IFRS, there are two important things that become important goal of this journal is the presentation of liabilities in the financial statements are described in more detail and uses two languages ??so that foreign investors can clearly read the entity's ability to pay its liabilities. The second point is likely to commit fraud on account of liability contained in the consolidated report will be smaller so that the stakeholders can see clearly the real situation and financial position of an entity. Keyword: Entity, Liabilities, Consolidation